Pedagogical regression through service-learning develops the holistic medical graduate by redefining reciprocity - Botha, R.; Bezuidenhout, J. (South African Journal of Higher Education, 2020)
Pedagogical regression through Service-learning uses dialogue and deliberation as active learning tools. Reciprocity is a consequence rooted in this engagement with diverse communities. The aim of the study was to analyse how reciprocity manifests during service-learning. Data collected from students, Grade 12 learners, radiography facilitators, and conference delegates were analysed. Students indicated that service-learning enhanced their learning through self-discovery and group interactions, but nothing academic was learned from the learners. They experienced personal growth and increased levels of social responsiveness. Grade 12 learners reported no educational exchange with the students. Radiography facilitators agreed that service-learning cultivates reciprocity through application of knowledge and elevates personal growth and social responsiveness in students. Conference delegates said that service-learning enhances the curriculum and cultivates social responsiveness in students. Reciprocity in service-learning is polygonal and needs to be redefined in terms of its equal mutualistic nature, of all communities benefitting from a broadly defined exchange.